Aplicación de la técnica de los “Mapas mentales” para desarrollar habilidades de comprensión y producción de textos en los estudiantes de 4to grado de primaria área comunicación integral de la I.E José Carlos Mariátegui de la FEH-R/UNSM-T - Saavedra Chávez, Paola Dorita (2010)
The investigation consisted on the application of the technique of the Mental Maps with the objective of developing the abilities of understanding and production of texts in the students of the fourth grade of primary education, in the area of Integral Communication of the Experimental Educational lnstitution José Carlos Mariátegui of the Ability of Education and Humanities - Rioja. The investigation arase because one could observe that at the present time models or techniques are not used systematized to read and to process the information of the texts and in view of the fact that the students read like they can: Sorne identifying main ideas of the paragraphs with sorne technical approach; other, copying th.e information literally or simply suppressing sorne lines of the text. This way, they hardly ever use outlines or graphic representatíons to translate the product of the reading and understanding of the text; neither they know how the Mental Maps are elaborated, among other techniques that you/they help him in their learning process. By the Hght of this reality, and based on the antecedents of the investigation, it was postulated that with the technique of the Mental Maps the students would develop their abilities for the understanding and production of texts, that which was constituted in the investigation hypothesis. As for the methodological part, one worked with a sample of 15 students to who you/they were administered a pretest to the beginning of The investigation and a postest after applying 7 leaming sessions based on the mental Maps. Regarding the results, the contrastación of the hypothesis was carried out with a leve! of trust of 95%, by means of the test t of Student for the paired difference te = 46.72 maijor score de tt = 1,761, accepted the investigation hypothesis, that which means that the application of the technique of the Mental Maps has developed the abilities of the understanding and production of texts significantly in the students of the 4° Grade of Primary Education of the Educationallnstitution "José Carlos Maríátegui"